Comparing the Vocational Interests of Arts and Science Freshmen using the Strong-Campbell Interest Inventory - Meuser, Dorothy M.; Edwards, Henry P. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study compares the vocational interests of University of Ottawa Arts and Science freshmen in terms of their Basic Interest scale scores on the Strong-Campbell Interest Inventory. Six discriminant function analyses were made using two groups at a time. A four-group discriminant analysis wasconducted between Arts males. Science males, Arts females, and Science females. In each stepwise analysis, significant differences in Basic Interests were found between Arts and Science freshmen as well as between sexes within these curricula. Prediction into group membership on the basis of the discriminant scores yielded more correct classifications than expected by prior group size probability.